The effects of childhood maltreatment on cyberbullying in college students: The roles of cognitive processes - Li, Man; He, Quanxing; Zhao, Jia; Xu, Zhansheng; Yang, Haibo (Acta psychologica, 2022)
Previous studies suggested that childhood maltreatment was associated with cyberbullying. However, it's not clear the internal cognitive processes of how maltreatment causes cyberbullying. Therefore, the current study aims to explore the effect of childhood maltreatment on cyberbullying and the mediating effects of hostile attribution bias and anger rumination. A sample of 528 college students completed the measures of childhood maltreatment, cyberbullying, hostile attribution bias, and anger rumination. Multiple mediation analysis and bootstrapping showed that hostile attribution bias and anger rumination mediated the link between child maltreatment and cyberbullying. The results of this study suggested that childhood maltreatment increased the risk of cyberbullying, which was caused by a co-effect of hostile attribution bias and anger rumination, and it provides an intervention direction for effectively preventing the cyberbullying in abused individuals. •Childhood maltreatment positively predicted cyberbullying through anger rumination.•Childhood maltreatment affects cyberbullying through hostile attribution bias and anger rumination.•The integrative cognitive model can explain the internal cognitive processes of cyberbullying in abused youth.